A consciência quântica: uma analogia entre Goswami e Plotino - Oliveira, Ronaldo de (2019)
Based on Goswamis’s monistic-idealistic philosophy, which proposes the Quantum Consciousness (Quantum Mind) as a mediating and unifying principle of all reality in its distinct facets, manifested or in a potential state, the quantum mind is in evidence as the core theme of this paper, establishing a correlation between Goswami and Plotinus. Using an understanding of quantum mechanics as a starting point, as it assumes that the observer role is vital to quantum measurement, the philosophical problem that guides this research is located in answering if there is any analogies between Goswami’s and Plotinus’ lines of thinking concerning Consciousness/the One, without restoring metaphysics of two worlds: physical and non-physical. Due to this problem statement, an overall goal was designed: establishing an analogy amidst Goswami and Plotinus. Its specific objectives are to analyze Goswami’s main concept of “quantum” consciousness in a philosophical approach; present the plotinian insight of the One as the founding superabundant principle from which all potentiality and manifested reality emanate; and lay the universal criteria to “quantum ethics” that arise from a close relation between the “quantum mind” and “responsibilities ethics” before the world and individuals. This research is justified, in a personal manner, by its given theoretical and yet practical challenge of integrating parted realms of human experience – science and ethics – through a unifying principle that could be applied as general guidance, thus to every single person. Its academic relevance is displayed due to the fact that quantum mechanics is theoretical basis to many technological breakthroughs and also in the view of lacking academic research showing the ethical implications that emerge from this new technically succeeded science frontier. Regarding its social pertinence is the effort to show that people are potentially connected with each other by a common source: the quantum mind. Therefore, the understanding of both the world and its fundamental structures may enable the right conditions for much proper ethical and educational praxis, supplying social demands from the 21st century and combining both philosophical and scientific knowledge. Hence, a critic bibliographical research method was applied, aiming the main part of Goswami’s body of word, being The self-aware Universe (2003) the focal point of the paper for providing the theoretical groundwork required in order to understand the researched theme, as the majority of the author’s further work relies on those bases. Excerpts of Plotinus’ Enneads will be employed in building an analogy between both thinkers, in order to justify the monistic-idealistic principle brought by this paper. Hopefully, the results of this research are going to demonstrate that: by expanding one’s extent of conscious perception an individual can make original choices based on an unviolated level, that is the quantum consciousness, becoming creative and responsible; the finding of self-awareness as a self-referring development of the Quantum Mind (Goswami) and of the One (Plotinus), if applied to education, has a direct impact on interpersonal relationships, because people can realize themselves as co-creators of reality, as conscious observers with self-reference and as subjects who by choosing creatively are able to shape the world in the same pace they shape themselves. Therefore, the investigation of this Ethics will apply a systemic approach including both dynamic and static elements and enunciate the dialectic of human life in its relations.